University’s Entrepreneurial Ecosystem and Involvement of Students in Entrepreneurial Activities: A Case of Universiti Tun Hussein Onn Malaysia (UTHM) - Miskam, Fauziah; Omar, Siti Sarah; Md Noor, Haris; Azizan, Anim Zalina; Hashim, Mohd Yussni; Ali, Norsaleha; Md Ariffin, Khadijah; Ahmed Al-Shameri, Ahmed Saleh; Hashim, Fazian (Qualitative Research Association Malaysia, 2020)
The concept of the entrepreneurial ecosystem refers to the interaction between the various stakeholders of institutions and individuals to encourage implementation towards entrepreneurship, innovation and the growth of Small and Medium Enterprises (SMEs). Universities play an important role in the entrepreneurial ecosystem for entrepreneurship and forms a catalyst for economic growth and capacity building to enhance the innovation, creativity and competitiveness of a country. The objective of this study was to explore the involvement of UTHM students in entrepreneurial activities based on the university’s entrepreneurial ecosystem in terms of financial assistance, infrastructure, education and training. The methodology employed for this study is a qualitative inquiry by using in-depth interview technique. The respondents consisted of 10 students and officers from the Centre of Business Entrepreneurship Development. The data were then being transcribed and analysed using thematic analysis. The results of this study showed that financial assistance, infrastructure, education and training is a very important ecosystem in increasing student involvement in entrepreneurship. The study also shows that there are inadequate infrastructure facilities to meet the demand of students for business. The lack of provision of loans also affected the level of student participation in entrepreneurship at the University.